Robust optimal usage modeling of product systems for environmental sustainability. Issue 3 (6th September 2018) - Ma, Jungmok
Graphical abstract: Abstract: Proper modeling of the usage phase in Life Cycle Assessment (LCA) is not only critical due to its high impact among life cycle phases but also challenging due to high variations and uncertainty. Furthermore, when multiple products can be utilized, the optimal product usage should be considered together. The robust optimal usage modeling is proposed in this paper as the framework of usage modeling for LCA with consideration of the uncertainty and optimal usage. The proposed method seeks to optimal product usage in order to minimize the environmental impact of the usage phase under uncertainty. Numerical examples demonstrate the application of the robust optimal usage modeling and the difference from the previous approaches.